Redescription of the early larval stages of the pandalid shrimp Chlorotocus crassicornis (Decapoda: Caridea: Pandalidae) - Landeira, Jose M.; Jiang, Guo-Chen; Chan, Tin-Yam; Shih, Tung-Wei; Gozález-Gordillo, J. Ignacio (Zootaxa, 2015)
The first four larval stages of the pandalid shrimp Chlorotocus crassicornis (A. Costa, 1871) are described and illustrated from laboratory-reared material obtained from ovigerous females collected in the southwestern Spain and south Taiwan. The second to fourth larval stages of this species are reported for the first time to science. Detailed examination of the first larval stages reveals that previous description misidentified some key larval characters which have prevented its identification in plankton samples. It is found that the zoeal morphology of Chlorotocus is not very different from other pandalid larvae, and in fact closely resembles Plesionika and Heterocarpus.